Plasma YKL-40 is associated with prognosis in patients with metastatic pancreatic cancer receiving immune checkpoint inhibitors in combination with radiotherapy - Johansen, Astrid Z.; Novitski, Sif I.; Hjaltelin, Jessica X.; Theile, Susann; Boisen, Mogens K.; Brunak, Søren; Madsen, Daniel H.; Nielsen, Dorte L.; Chen, Inna M. (Frontiers in Immunology, 2023)
Background. YKL-40, also known as chitinase-3-like protein 1 (CHI3L1), is a secreted glycoprotein produced by various cell types including stromal, immune, and cancer cells. It contributes to cancer progression through tumor-promoting inflammation and has been shown to inhibit the cytotoxicity of T and NK lymphocytes. In vivo studies have demonstrated synergistic anti-cancer effects of blocking YKL-40 in combination with immune checkpoint inhibitors (ICIs). Biomarkers for the prediction of the response to ICIs are highly needed. We investigated the association between plasma YKL-40 and clinical benefit and survival in patients with metastatic pancreatic cancer (mPC) receiving ICIs and stereotactic body radiotherapy (SBRT).Methods. Blood samples were collected from 84 patients with mPC who participated in the randomized phase II CheckPAC study, in which patients received nivolumab with or without ipilimumab combined with a single fraction of SBRT. Plasma YKL-40 was measured using a commercial ELISA kit.Results. Elevated baseline plasma YKL-40 was an independent predictor of shorter overall survival (OS) (HR 2.19,. A ≥ 40% decrease in plasma YKL-40 during treatment was associated with longer progression-free survival (p = 0.009) and OS (p = 0.0028). There was no This is a provisional file, not the final typeset article correlation between plasma YKL-40 and the tumor burden marker CA19-9 at baseline or during treatment.This study contributes new knowledge regarding YKL-40 as a predictor of clinical benefit from ICIs and radiotherapy. These exploratory results warrant further investigation of YKL-40 as a biomarker for patients treated with immunotherapies.